PEMBUATAN APLIKASI PEMBELAJARAN BAHASA JEPANG LEVEL DASAR BERBASIS ANDROID - Lisania Ayu Agustin; Budi Hartanto; Melissa Angga (Perpustakaan Universitas Surabaya, 2018)
In this era of globalization, make the country Indonesia to connect with other countries in various countries in the world. One of the countries that have relations with Indonesia and plays an important role in various aspects in Indonesia, especially in terms of economics and education is the country of Japan. The obstacles that must be overcome so that the relationship between Indonesia and other countries can be well established is about language. Basic Level of Japanese Language Learning Applications, built to help learners of basic level Japanese language can write, read, and understand Japanese easily. This app utilizes android technology. Android has many Application Programming Interface (API) tools for application development, one of which is the Gesture API feature. By utilizing the API was built the application of Japanese Language Learning, mainly in Japanese letters, both Hiragana and Katakana. This application is designed and built using android programming languages and MySQL database as its storage database. The results achieved is a learning application that provides ease in understanding Japanese language. This learning application is supported by multimedia so as to provide an interesting and interactive appearance, so that users can understand what is learned.